Review of Hanushek "Making Schools Work" - Gintis, Herbert (Education Policy Analysis Archives, 1995)
Making Schools Work is about the economics of educational policy. The Brookings Institution, publisher of the volume, is among the most respected institutions of economic policy research in the United States. The analysis and recommendations offered by Eric Hanushek, Professor of Economics at the University of Rochester, are based on original research financed by the Pew Charitable Trusts, and carried out by a distinguished group of economists.